2007
DOI: 10.1007/s00167-007-0420-y
|View full text |Cite
|
Sign up to set email alerts
|

Improved accuracy of component alignment with the implementation of image-free navigation in total knee arthroplasty

Abstract: Accuracy of implant positioning and reconstruction of the mechanical leg axis are major requirements for achieving good long-term results in total knee arthroplasty (TKA). The purpose of the present study was to determine whether image-free computer navigation technology has the potential to improve the accuracy of component alignment in TKA cohorts of experienced surgeons immediately and constantly. One hundred patients with primary arthritis of the knee underwent the unilateral total knee arthroplasty. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
59
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 44 publications
8
59
0
Order By: Relevance
“…This finding is also intuitive because surgeons would be able to place the cutting block independently of the anatomy whether a standard extramedullary guiding system or a navigation system is used. Numerous studies have documented the use of navigation improves alignment [12,22,24,28,34,37], but relatively few previous studies have addressed the issue of navigation in the context of the alignment of knees with severe deformity [12,22,24,28,34,37]. Our findings are generally in accord with two previous studies, which found that the use of navigation reduces outliers in knees with severe deformity [12,22,24,28,34,37].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is also intuitive because surgeons would be able to place the cutting block independently of the anatomy whether a standard extramedullary guiding system or a navigation system is used. Numerous studies have documented the use of navigation improves alignment [12,22,24,28,34,37], but relatively few previous studies have addressed the issue of navigation in the context of the alignment of knees with severe deformity [12,22,24,28,34,37]. Our findings are generally in accord with two previous studies, which found that the use of navigation reduces outliers in knees with severe deformity [12,22,24,28,34,37].…”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies have documented the use of navigation improves alignment [12,22,24,28,34,37], but relatively few previous studies have addressed the issue of navigation in the context of the alignment of knees with severe deformity [12,22,24,28,34,37]. Our findings are generally in accord with two previous studies, which found that the use of navigation reduces outliers in knees with severe deformity [12,22,24,28,34,37]. Furthermore, in the present study, the navigation group also had no outliers in femoral or tibial component alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have also been reported in a meta-analysis of level-I studies [6]. Unfortunately, the total time spent in the operating room and the lack of clinical amelioration has tempered its uniform acceptance by the surgical community [3,14].Patient-specific instruments (PSI), recently introduced as a new technology, could demonstrate the same advantage of navigation in increasing accuracy, but without the practical inconveniences such as, the need to perform anatomical mapping or to position trackers during the procedure [10].The virtual planning of the TKA procedure is outsourced to engineers who identify the anatomical landmarks needed for alignment on CT/MRI based 3D models, after which the information is transferred to patient-specific instruments that can be used during surgery. These instruments, created by laser sintering, can be produced in the most complex forms and are thus patient specific [1,5].…”
supporting
confidence: 66%
“…Numerous studies report use of a computer-assisted navigation system limits the prevalence of outlier values of limb and/or implant alignment measurements in the coronal plane [2,5,8,9,12,14,21,30,32,37]. Whether the same benefits are realized in the sagittal plane when a surgical navigation system is used is unclear [2, 6-8, 12, 18, 32].…”
Section: Introductionmentioning
confidence: 99%